2007
DOI: 10.1007/s00420-007-0280-2
|View full text |Cite
|
Sign up to set email alerts
|

Atopy, symptoms and indoor environmental perceptions, tear film stability, nasal patency and lavage biomarkers in university staff

Abstract: BUT and NAL-lysozyme was associated with ocular, nasal, laryngeal symptoms and indoor environmental perceptions. Ever having had asthma and ever having had hay fever were predictors for symptoms and perceived air quality, respectively. Phadiatop, Total IgE, familiar allergy and ever eczema were not associated to symptoms or perceived environments. Age, gender and Phadiatop were main predictors for ocular and nasal biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
14
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 49 publications
5
14
1
Order By: Relevance
“…With regard to moving into a newly built house, studies in Japan have recently identified chemical substances emitted from indoor building materials, such as formaldehyde and volatile organic compounds as major causes of sick building syndrome [28,29]. These chemicals may thus increase the risk of allergic disease [30] and several studies reported a correlation between AD and sick building syndrome [31,32]. …”
Section: Discussionmentioning
confidence: 99%
“…With regard to moving into a newly built house, studies in Japan have recently identified chemical substances emitted from indoor building materials, such as formaldehyde and volatile organic compounds as major causes of sick building syndrome [28,29]. These chemicals may thus increase the risk of allergic disease [30] and several studies reported a correlation between AD and sick building syndrome [31,32]. …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, unbalanced psychosocial work environment (Marmot et al, 2006;Runeson et al, 2006) and occupational stress (Azuma et al, 2014;Bakke et al, 2007) have been shown to be related to SBS symptoms. Indoor environmental factors associated with SBS include room temperature (Bakke et al, 2008), relative air humidity (Wolkoff, 2008), building dampness (Mendell et al, 2011;Park et al, 2008), ventilation flow (Seppänen and Fisk, 2004;Sundell et al, 2011), microbial exposure such as molds and bacteria (WHO, 2009), microbial volatile organic compounds (MVOC) (Araki et al, 2010;Sahlberg et al, 2013) and volatile organic compounds (VOC) (Takigawa et al, 2012).…”
mentioning
confidence: 99%
“…They include food intolerance, unexplained episodes of fever, allergies, urticaria or angioedema, skin sensitivity to sunlight, oral ulcerations, inflammation in distal joints or livedo reticularis. These associations can support an immunologic mechanism for SBS [17,18]. A multivariate score for predicting the RC's Disease has been constructed; such a score requires further validation in independent samples before it can be considered applicable in other places.…”
Section: Discussionmentioning
confidence: 99%